Religious Ethics on Industrialization: A Discourse from Islamic Perspective - Mohd Khairul Nizam Zainan Nazri; Mahmud Ahmad; Nurul Jannah Zainan Nazri; Mardiana Bt Mat Ishak; Mohd Akmal Sidik; Khadijah Mohd Khambali @ Hambali (International Digital Organization for Scientific Information (IDOSI), 2024)
Volume: , 2 Issue (page: 146-157)